2006
DOI: 10.1093/cercor/bhl138
|View full text |Cite
|
Sign up to set email alerts
|

Receptive Fields in Human Visual Cortex Mapped with Surface Electrodes

Abstract: Most of our understanding of the functional organization of human visual cortex comes from lesion and functional imaging studies and by extrapolation from results obtained by neuroanatomical and neurophysiological studies in nonhuman primates. Although some single-unit and field potential recordings have been made in human visual cortex, none has provided quantitative characterization of spatial receptive fields (RFs) of individual sites. Here we use subdural electrodes implanted for clinical purposes to quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
122
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(145 citation statements)
references
References 53 publications
21
122
2
Order By: Relevance
“…Thirdly, crosscorrelation analysis revealed that the mean response latency in Area 17 was slightly earlier than that observed in Area 18 and significantly earlier than responses in Area 19 (Pb.01). This trend is consistent with a recent study where visual stimuli were presented to subjects (selected for clinical purposes) with subdural electrodes implanted over different regions of the visual cortex [36], as well as with signal arrival times recorded across distinct visual regions in nonhuman primates [37]. Taken together, these EEG source imaging results indicate that the artifact-correction methodology correctly identified and removed unwanted nonneural components of the EEG signal while preserving those containing information which reflected the movie stimulus.…”
Section: Discussionsupporting
confidence: 90%
“…Thirdly, crosscorrelation analysis revealed that the mean response latency in Area 17 was slightly earlier than that observed in Area 18 and significantly earlier than responses in Area 19 (Pb.01). This trend is consistent with a recent study where visual stimuli were presented to subjects (selected for clinical purposes) with subdural electrodes implanted over different regions of the visual cortex [36], as well as with signal arrival times recorded across distinct visual regions in nonhuman primates [37]. Taken together, these EEG source imaging results indicate that the artifact-correction methodology correctly identified and removed unwanted nonneural components of the EEG signal while preserving those containing information which reflected the movie stimulus.…”
Section: Discussionsupporting
confidence: 90%
“…9). Third, pRF size estimates across the visual cortex agree with estimates acquired using cortical surface electrodes in humans (Yoshor et al, 2007). stimuli were 3 s in duration and separated by 30-s intervals.…”
Section: Resultssupporting
confidence: 65%
“…In addition, the fMRI-pRF sizes are comparable to human electrophysiological measurements estimated using surface electrode with a 2.2-mm-diameter recording area (Yoshor et al, 2007). Yoshor et al (2007) report pRF sizes in early visual cortex, roughly corresponding to V1/V2, as σ = 0.76°± 0.23°.…”
Section: Comparisons Of Human Prf and Neuronal Receptive Fieldssupporting
confidence: 65%
See 1 more Smart Citation
“…Experimental techniques with high temporal resolution, including scalp electroencephalography, magnetoencephalography (MEG), and intracranial recording in neuropsychological patients, report the earliest cortical response recorded to any visually presented stimulus occurs at latencies ranging from 50 to 100 ms after stimulus onset (Martínez et al, 1999;Furey et al, 2006;Yoshor et al, 2007). Other studies examining high-level visual object recognition report a selective response for specific object categories, including faces and bodies, beginning 100 -200 ms after stimulus onset (Bentin et al, 1996;Thorpe et al, 1996;Eimer, 1998;Allison et al, 1999;Liu et al, 2002Liu et al, , 2009Furey et al, 2006;Thierry et al, 2006;Engell and McCarthy, 2010).…”
Section: Introductionmentioning
confidence: 99%